3D nitrogen-doped graphene aerogels as efficient electrocatalyst for the oxygen reduction reaction. (November 2018) - Xue, Qi; Ding, Yu; Xue, Yuanyuan; Li, Fumin; Chen, Pei; Chen, Yu
Abstract: Heteroatom-doped carbon nanomaterials are highly promising cost-effective electrocatalysts for replacing noble metal nanomaterials in many energy-related electrocatalytic fields. Herein, the nitrogen-doped graphene aerogels (N-GA) with tunable nitrogen content are synthesized by the pyrolysis of the graphene aerogels-polyallylamine (GA-PAA) hybrids. By changing the molecular weight of PAA in the GA-PAA hybrids, the nitrogen content of the N-GA can be regulated from 0.58% to 2.07%. The electrocatalytic activity of the N-GA increases with the nitrogen content for the oxygen reduction reaction (ORR) in the alkaline media. The three-dimensionally porous interconnected structure and the nitrogen doping endow the N-GA with excellent electrocatalytic activity and durability for the ORR in the alkaline media. Graphical abstract: Image 1